INSTALLATION OF BOTTOM FISHING AFFAIRS AS AN EFFORT TO IMPROVE FISH CATCHES IN BILUHU TIMUR VILLAGE, GORONTALO - Suherman, Sutianto Pratama; Juliana, Juliana (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2025)
Biluhu Timur Village is one of the coastal villages located in Gorontalo Regency, with most of its residents working as fishermen. However, limited fishing gear and technology cause fishermen's catches to be less than optimal. Therefore, community service activities were carried out in the form of installing bottom fish aggregating devices (FADs) as one solution to increase fish catches. Bottom fish aggregating devices (FADs) are artificial structures installed on the seabed and function to attract and collect fish. The activity methods include socialization, training in making FADs, and installing FADs at predetermined strategic locations. The results of the activities showed that the use of bottom fish aggregating devices (FADs) had a positive impact on increasing fishermen's catches. Fish such as white snapper, rabbitfish, grouper, and kuwe were found in greater numbers around FADs. In addition to providing economic impacts, the use of FADs also supports sustainable fish resource management.